Diseño de una Cartilla de finanzas personales a mujeres rurales de la vereda la Maria. (2021)
Personal finances are fundamental in the economy of a person and are associated with financial education as a support for personal development and the environment through learning that allows decision-making, the proper management of expenses and benefits in the determinations financial tools, which are very useful tools that help women in the rural sector to obtain greater skills in the management of productive and economic processes. Based on this, the objective of this project is to design a primer that contributes to the teaching of personal finance for women in the rural sector, for which the descriptive and qualitative methodology will be used, the information will be collected through a In the survey, the data obtained will be tabulated in a statistical program, later the structure of the booklet will be defined and finally it will be designed and disseminated in the village of La María that allows them to learn, understand and manipulate financial concepts with greater skill.